Locusi, Illocusi, and Perlocusi Speech Acts in Ustad Hannan Attaki's Sharing Time event on the Youtube First Shof Media Indonesia Channel - Hikmah; Nurul Qomariyah (Penerbit Hellow Pustaka, 2024)
In the current era, the use of YouTube media has increased very rapidly, this is because access is very easy. One of the YouTube content that is currently popular among the Muslim community is Ustad Hannan Attaki's sharing time content uploaded by the First Shof Media Indonesia Youtube Channel. This speech act also occurs in sharing time events, which can cover several topics ranging from questions about religious issues, mental health, to in-depth conversations with famous religious figures. In this study, researchers studied one of the sharing times with the sub-theme